DEVELOPMENT OF MALAYSIAN STUDENT SELF - LEADERSHIP MODEL: A DESIGN AND DEVELOPMENT RESEARCH - Mustafa Edria Nita; A. Ghani Muhammad Faizal (Jurnal Akuntabilitas Manajemen Pendidikan, 2022)
The modified Delphi Technique (MDT) is one of the phases in Design and Development Research (DDR). It is a systematic method of tool development and validation. Realizing the potential of this technique, this article aims to expose other researchers to using  MDT. The MDT is applied in phase 2 which is the development and design process of a model. Agreement of 17 experts about the domains was obtained from the process of round 1 (interview), round 2 (questionnaire) and round 3 (fuzzy Delphi Method). The credibility of the research can also be determined using the Cohen Cappa coefficient. To summarize, the application of the MDT to research requires expert consensus through a clear procedure to ensure valid and reliable research findings. The domains and sub-domains acquired are not only focused on knowledge but also include behaviors and values.  The results from this research seek to obtain  to obtain expert consensus regarding the domains and sub-domains needed in student self-leadership. The research findings are in the form of discussion regarding the process balance and the study design using the MDT. This MDT balance can be seen through and suitable for qualitative and quantitative studies.